"Does the Color of Your Skin Make You American?:" Immigrant Parents' Responses to History Texts in the New South. Issue 3 (3rd July 2019) - Noguerón-Liu, Silvia
Abstract : This article describes the ways positioning theory is used to examine the reading responses of immigrant parents to texts about the contributions of historical figures of nondominant backgrounds. I explain how theories of positioning and identity can inform citizenship and social studies education; in particular, programs serving Latinx and immigrant students of diverse backgrounds. I then apply a positionality lens to examine immigrant parents' responses to texts about César Chavez' background, and to their responses to books about the Civil Rights Movement. I show how they discuss the intersection of race, citizenship status, and allegiance to the nation-state, positioning historical figures in relation to these concepts, and to narratives of injustice (present and past) across countries. I present implications for critical questioning of history texts in the classrooms, leveraging the knowledge and perspectives of diverse families and communities.